Pengaruh Karakteristik Petani Padi terhadap Tingkat Partisipasi dalam Program KUR Tani di Desa Tempuran Kecamatan Trimurjo Kabupaten Lampung Tengah - Khotimah, Khusnul; Nurmayasari, Indah; Listiana, Indah; Ibnu, Muhammad (Suluh Pembangunan : Journal of Extension and Development, 2024)
Participation is a spontaneous involvement with awareness accompanied by responsibility for the interests of achieving common goals. Participation cannot stand alone, there must be factors that influence it, one of which is individual characteristics. This research aims to know the factors that influence participation, the effect of level of farmer characteristics to participation, and the effect of participation of rice farmers in KUR Tani program. This research was conducted in Tempuran Village, Trimurjo District, Central Lampung Regency. Trimurjo District is the first sub-district to be used as a trial for the implementation of the Farmer's People's Business Credit (KUR) program. The census method is the method used in this study with a total sample of 70 farmers. Quantitative descriptive analysis and multiple linear regression analysis were used in this study. The results showed that the level of education and level of knowledge had a significant effect on the level of farmer participation in the KUR Tani program. Meanwhile, age, length of farming and motivation have no effect on the level of participation of rice farmers in the KUR Tani program.